(untitled) (Global Journal of Management and Business Research, 2020)
Recent developments in crypto currency have heightened the emerge and development of new form of money generally and crypto currency particularly. This development has reach to the precious metal which is historically known as a money. Reusing precious metal as a money by benefiting from crypto currencies technology is perceived to be an innovation in the current payment system that abandoned precious metal as a money since 1973. Therefore, the major aim of this research is to investigate in the potential users#x2019; tendency to adopt a Shar#x12B;#x2BF;ah-compliant precious metal backed crypto currency. The methodological approach adopted in this study is a quantitative method using questionnaires that was built based on the original model of innovation diffusion theory which consists of five factors. The analysis was conducted based on data elicited from 92 questionnaires using PLS-SEM. Overall,